Estudio de la realidad agrosocioeconómica y alternativas de desarrollo para las microcuencas de los ríos: Santiago y San Lucas del cantón Loja - Iñiguez Loján, Alex Javier (2015)
This research is about ¨ESTUDIO DE LA REALIDAD AGROSOCIOECONÓMICA Y ALTERNATIVAS DE DESARROLLO PARA LAS MICROCUENCAS DE LOS RÌOS SANTIAGO Y SAN LUCAS, DEL CANTÓN LOJA¨, it has as main purpose to evaluate the agro-socioeconomic factors of the micro-hollows of the rivers: Santiago and San Lucas from the Loja canton, systemize the agro-socioeconomic problematic identified in the zone, which was analyzed, and it was developed an improvement plan to manage the productive factors through participative processes in the communities of the Micro-hollows. It was used many tools to this work such as bibliographic reviews, documentaries, walks, population census, informal conversations with the farmers, meetings of work with the parish leaders, students, teachers, etc., workshops to elaborate the FODA plan and the results were socialized. The improvement plan and manage of the productive factors, through participative process of solution is a determinant factor of success of the competitiveness of each community which have micro-hollows. It provides an operative and functional methodology; it is illustrating step by step the conclusive aspects to the practice. It will benefit in global way to the population. It provides intellectual and effective tools to organize the tasks, to build the knowledge and the efficient development, according to the exigencies of the actual and productive society with the objective to improve the conditions to the life, which contributes to the Good Life. I can conclude that the actual environmental situation in Santiago and San Lucas micro-hollows are closely related to the activities that their habitants do in their lands. The high lands of the micro-hollows present big potentialities such as: runoff of water, flora and fauna, favorable climate to develop agriculture, it is because of the variety of zones that they have, meanwhile in the middle and low lands of the micro-hollows present erosion of the soil, the use of agrochemicals, to increase border of the agricultural-livestock, deforestation and pollution of the environment. It is recommended to consider the social interest as: the dotation of drinkable water, dwelling, health, productive activities, eco-touristic and agro-touristic projects, trainings to the farmers, as strategic activities and the motor of the local development, to get advantage of the natural and artificial capacities and potentialities which these lands offer.